DESIGNING THE INFLUENCE OF OPERATIONAL AND RHEOLOGICAL INDICATORS OF GLYCERIN IN MARZIPAN PASTES - Fedoriv, Viktor; Piddubnyi, Volodymyr; Stadnyk, Igor; Diichuk, Volodymyr (SWorld-Ger Conference proceedings, 2025)
The article discusses the problems of using demineralized whey powder and glycerin on the characteristics of model compositions of marzipan pastes. To achieve this goal, the addition of various fillers to the composition of candy masses, which enrich the